Subcritical Water and Pressurised Ethanol Extractions for Maximum Recovery of Antioxidants from Orange Peel Herbal Dust with Evaluation of Its Pharmacological Potential Using In Silico and In Vitro Analysis - Slađana Krivošija; Ana Ballesteros-Gómez; Mire Zloh; Nataša Milić; Aleksandra Popović; Nataša Nastić; Senka Vidović (Antioxidants, 2025)
This research explored the potential of pressurised liquid extraction techniques for valorising herbal orange peel dust (OPD) waste from the filter tea industry. A series of experiments were conducted, varying the temperature (120–220 °C) and solvent (water and 50% (v/v) ethanol), while pressure and time were kept constant. Afterward, the obtained extracts were analysed by LC-ESI-MS/MS for determining the chemical composition. The highest concentrations of the most dominant compounds, the antioxidants hesperidin (662.82 ± 22.11 mg/L) and naringin (62.37 ± 2.05 mg/L), were found at specific temperatures using subcritical water extraction. In silico studies indicated that these compounds could interact with sirtuin-1 and growth factor beta receptors, suggesting potential anti-ageing benefits for skin. In vitro experiments on rat hepatoma cells (H4IIE) revealed that OPD extracts had antitumor potential, inhibiting cell proliferation and altering cell morphology. These findings underscore the importance of temperature and extraction technique in obtaining antioxidant-rich extracts with pharmacological potential. The resulting extracts, obtained using green solvents, show promise for cosmetic applications, though further in vivo studies are needed to confirm their therapeutic efficacy.